MEASURING SERVICE QUALITY USING ANALYTICAL HIERARCHY PROCESS (AHP) IN THE LIFE INSURANCE INDUSTRY IN MANADO - Mawuntu, Sylverson Frandy J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Life insurance industries become a very competitive and attractive. They not only focuses product but focus on maintaining service quality especially in manado. There two major life insurance in manado that is PT. Allianz life insurance and PT. Prudential life assurance. Each life insurance must to survive and gain profit through satisfy their customer in different way. This study aimed to find out who is the performer life insurance in relation with service quality using analytical hierarchy process and to identify the strength and weaknesses point of each life insurance trough the questioner that given to the customer that have experience with those two life insurance.AHP is a method for ranking decision alternative and selecting the best one when the decision maker has multiple objectives, or criteria, on which to base the decision. The result shows that the best performer life insurance relation with service quality in manado is Allianz. Overall the criteria that given Allianz is the best performer life insurance in relation with service quality measurement model and the most preferred life insurance over Prudential. Since Allianz as the best performer in service quality but not consistently, Allianz has keep maintaining their performance in services so that they can keep dominate the market. And Prudential has to re-evaluate, find innovative products and gave the best service to the customer. Keywords: service quality, life insurance, analytical hierarchy process